Effects of vineyard ‘potential’ and grape maturation on the aroma-volatile profile of Grenache wines - Ana Escudero (OENO One, 2019)
Background and aims: Wine is a beverage characterized by its pleasant aromatic features. These sensory notes are determined by the specific concentrations of odorous chemical compounds in each wine. Many of these aroma compounds arise directly or indirectly from the grapes, and their formation is affected by both grape metabolism and the viticultural ecosystem. Two studies were done with the 2015 vintage of Vitis vinifera L. cv. Grenache in Denominación Origen Somontano, a wine region of northern Aragon, Spain. In one study, we analysed wine from vineyards with different potentials: high potential, defined by balanced yield and high exposed leaf area (surface foliaire exposée, SFE, expressed in square metres) relative to production (P, expressed as kilograms of grapes) (i.e. high SFE:P ratio); and low potential, defined by unbalanced yield and low SFE:P ratio. In the other study, we analysed wine produced from grapes harvested at different times and therefore at different stages of ripening. The aim was to determine the effects of these variables on the aromatic compound profile of the wines.